Efektivitas Konfigurasi Perkuatan Ferosemen terhadap Reduksi Tegangan Tarik Maksimum Struktur Rumah Sederhana Tak Terkekang - Kuswiantoro, Mahendra Septa; Karisma, Dwifi Aprillia; Nursandah, Fauzie (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
homes, especially those without adequate structural components, known as un-engineered houses. These houses rely solely on brick masonry walls as load-bearing elements and are unable to effectively resist seismic forces. In Blitar Regency, many homes are constructed without technical planning, relying only on brickwork for structural support. This situation highlights the need for economical reinforcement technology suitable for simple houses owned by low-income communities. This study aims to determine the most effective critical reinforcement design using a ferrocement layer on the behavior of simple house structures with unconfined brick walls. Numerical simulations were performed using Time History Analysis, with variations in earthquake intensity of 30%, 60%, 100%, and 150%, and ferrocement reinforcement widths of 300, 400, 500, and 600 mm. The D2 reinforcement model proved to be the most effective, showing a strength reduction ratio close to the allowable critical limit of 0.79. The analysis also indicates that wider reinforcement increases the building’s strength but decreases material use efficiency. These findings provide important insights into balancing structural performance and economical material utilization for reinforcing un-engineered masonry homes vulnerable to earthquake damage.